2022
DOI: 10.1038/s41467-022-30932-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic amyloidogenic peptides in the proteome of SARS-COV2: potential implications for neurological symptoms in COVID-19

Abstract: COVID-19 is primarily known as a respiratory disease caused by SARS-CoV-2. However, neurological symptoms such as memory loss, sensory confusion, severe headaches, and even stroke are reported in up to 30% of cases and can persist even after the infection is over (long COVID). These neurological symptoms are thought to be produced by the virus infecting the central nervous system, however we don’t understand the molecular mechanisms triggering them. The neurological effects of COVID-19 share similarities to ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(106 citation statements)
references
References 64 publications
4
102
0
Order By: Relevance
“…to have amyloidogenic potential (35,36). Similar findings have been previously demonstrated for HSV-1, where HSV-1 reactivation was shown to increase AD risk (37), and HSV-1 infection was shown to induce amyloid aggregation in animal models (20,38,39).…”
Section: Discussionsupporting
confidence: 80%
“…to have amyloidogenic potential (35,36). Similar findings have been previously demonstrated for HSV-1, where HSV-1 reactivation was shown to increase AD risk (37), and HSV-1 infection was shown to induce amyloid aggregation in animal models (20,38,39).…”
Section: Discussionsupporting
confidence: 80%
“…In ME/CFS (Myalgic Encephalomyelitis/Chronic Fatigue Syndrome), autoimmunity is well described [ 94 ]; and might also play an important role in long COVID because some autoantibodies share elements of epitope with the SARS-CoV-2 virus [ 99 ]. It has also been suggested that some of the viral sequences are amyloidogenic [ 100 , 101 ]. Viral persistence may play a key role in patients suffering from long COVID [ 102 ], and therefore driving an ongoing immune response or the development of autoimmunity (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A propensity to develop microthrombi in PASC has obvious implications for the pathogenesis of cardiovascular problems discussed above. Intriguingly, it has been suggested that the SARS-CoV-2 proteome includes amyloidogeneic peptides which may contribute to neurological symptoms [ 82 ].…”
Section: Pathogenesis and Biomarkersmentioning
confidence: 99%